The Use of Scientific-Based Approach in ELT Class to Improve Students’ Achievement and Classroom Interaction - Haerazi, Haerazi; May Vikasari, Rully; Prayati, Zukhairatunniswah (Register Journal, 2019)
ABSTRACTThis study investigated the use of the scientific-based approach in the ELT class to solve students' learning problems. Those problems are students' difficulties to complete their learning tasks, lack of vocabularies to complete reading tasks, lack of grammatical competence, afraid of proposing questions, afraid of speaking, and difficulties to complete the listening tasks. These caused students to have low achievement and inactive classroom interaction. The study was aimed at improving students' achievement and classroom interaction of 8th-grade students of SMPN 4 Praya, Central Lombok, West Nusa Tenggara. This study was classroom action research. The procedure of actions included two steps, namely the reconnaissance and the action. The reconnaissance presented the students' learning problems and the action consisted of four stages, namely planning, implementing, evaluating, and reflecting. The research instruments of this study used observation sheets, a questionnaire, and a test. The collected data were analyzed quantitatively and qualitatively. The result of this study showed that the use of the scientific-based approach was able to improve students' achievement and classroom interaction. The students' average score was 82.76. Each student' score was higher than the minimum passing grade (70). Meanwhile, the interaction classroom was active. It was supported by significant changes. Those changes were that students become more cooperative, active, and optimistic to complete reading tasks, listening tasks, speaking activities, and writing assignments in the form of group discussion. Keywords: Scientific-Based Approach, Achievement, Classroom Interaction